TAPHONOMY OF AMMONITE ASSEMBLAGES FROM THE MIDDLE-UPPER OXFORDIAN (TRANSVERSARIUM? - BIFURCATUS ZONES) IN THE INTERNAL PREBETIC (BETIC CORDILLERA, SOUTHERN SPAIN): TAPHONIC POPULATIONS AND TAPHOFACIES TO SUPPORT ECOSTRATIGRAPHIC INTERPRETATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The taphonomic analysis conducted on ammonoid assemblages has proven useful for palaeobiological and palaeoenvironmental reconstructions in upper Middle-to-lower Upper Oxfordian epicontinental deposits of the Internal Prebetic (southern Spain). Taphonic populations close to type I indicate the proximity, even coincidence, of life areas for neritic ammonites (i.e. parautochthonous assemblages). The relationships among preservation mode, shell size, within-bed position, corrasion, fragmentation, and epibionts (encrustment included), with lumpy-oncolitic and condensed & bioclasts-rich lumpy-oncolitic limestones allows us to typify two taphofacies. Taphofacies I shows higher values of mean shell size, corrasion, epibionts and encrustments, as well as a high number of specimens in quasi-horizontal settlement. The opposite characteristics serve to identify Taphofacies II. Taphonomic features, taphofacies and lithofacies combine in coherence with progressing third-order transgressive-to-highstand system-tract conditions and the resulting ecostratigraphic trends, which are registered by fluctuations in ammonite assemblages.